Iron(III) complexation with barbituric and 2-thiobarbituric acids in aqueous solution - Lakeev, Alexander P. (Russian journal of inorganic chemistry)
Complexation in systems containing iron(III) chloride and barbituric (H2BA) or 2-thiobarbituric (H2TBA) acid has been studied by spectrophotometry and pH-metry in the pH range of 1.3-3.3 (I = 0.1 (NaCl), t = 20°C). The presence of 1 : 1 complex particles with both mono- and deprotonated forms of the ligand has been established, and their stability constants (in log units) have been determined: [FeHBA]2+(3.49 ± 0.15), [FeHTBA]2+ (2.69 ± 0.07), [FeBA]+ (12.22 ± 0.13), and [FeTBA]+ (11.05 ± 0.08). It has been shown that the higher thermodynamic stability of barbiturate complexes compared to 2-thiobarbiturate complexes is due to the greater basicity of the barbiturate anion. Based on the stability constants obtained, it has been proposed to use orthophosphate, fluoride, and ethylenediaminetetraacetate ions to eliminate the interfering effect of iron(III) in the determination of malondialdehyde by the thiobarbiturate method. Orthophosphoric acid is the most convenient for practical applications, as it makes it possible both to mask iron(III) and to create a strongly acidic medium necessary for the formation of a colored malondialdehyde-H2TBA adduct.